ANALISIS MODEL PERPARKIRAN DALAM PERSPEKTIF EFEKTIFITAS RUAS JALAN DI KABUPATEN SUMBAWA, PROVINSI NUSA TENGGARA BARAT - Siti Nur Fadlilah; Yogi Arisandi (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2017)
Parking in Sumbawa District, West Nusa Tenggara nowdays has not provided significant problems yet to traffic congestion in some roads in Sumbawa District, but in some places with activities of trading, shopping and service centers will provide potential congestion in the next few years if there is no professionally improvement in parking management. This is due to inadequate parking facilities, manually parking systems, limited quality of the parking attendants and supervision that is less than optimal. The purpose of this study is to identify the characteristics of on-street parking and the potential income of parking charge in Sumbawa District. The analysis method used is descriptive qualitative and quantitative. The expected result of this study is the identification of on-street parking characteristics and the potential income of parking charge to support the performance of parking and smoothness of urban traffic in Sumbawa District.